009 Abnormal blood-brain barrier permeability in progressive multiple sclerosis. Issue 6 (27th May 2022) - Varatharaj, Aravinthan; Darekar, Angela; Gawne-Cain, Mary; Cramer, Stig P; Larsson, Henrik BW; Galea, Ian
Abstract : Disruption of the blood-brain barrier (BBB) is a hallmark of multiple sclerosis (MS). In clinical practice this is detected using contrast-enhanced magnetic resonance imaging (MRI). There is biochemical evidence, based on cerebrospinal fluid protein assays, to suggest that BBB permeability is associated with disease severity and may be greater in progressive than in relapsing-remitting disease. Therefore, it is paradoxi- cal that when using conventional contrast MRI the detection of focal BBB disruption is relatively rare in progressive MS. A diffuse low-level BBB leak in progressive MS is hypothesised to explain this apparent discrepancy. Our group is investigating the use of dynamic contrast-enhanced MRI (DCE-MRI), which enables the quantification of subtle BBB disruption. Here we present a small case series of DCE-MRI in people with progressive MS as well as age-matched healthy controls. Diffuse low-level BBB leakage is demonstrated in the brains of people with progressive MS, which is invisible to conventional MRI. We discuss the implications of these early findings for our understanding of disease biology, as well as the search for an effective treatment for disability progression. a.varatharaj@soton.ac.uk